Factors affecting drinking water vaccination intake in commercial poultry farms - Chong, M. Y. V.; Nik Mohd Azmi, Nik Mohd Faiz; Lee, J. E. (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
Vaccines are important means of prevention and control of poultry diseases worldwide. Drinking water vaccination remains as one of the most common mass vaccine administration methods. Its efficiency relies on the vaccinated water consumed by the chickens. This study aims to determine the success rate of drinking water vaccination of commercial poultry farms in Malaysia and to evaluate factors affecting such practice. 5 poultry farms that would undergo drinking water vaccination were selected for study. Prior to vaccination, blue dyes (Cevamune®) were added in the drinking water tank and farm parameters were recorded. 2 hours post vaccination, 100 to 250 chickens (1% of house population) were randomly sampled and evaluated for vaccine intake. From the study, only 10% of the houses fulfilled the requirement of yielding a minimum of 90% positive vaccine intake. Result further revealed that ambient temperature, water restriction hours, stocking density, age of chick, and effort of workers to chase chicks during vaccination, have significantly (p>0.01) affected the outcome of drinking water vaccination which could be due to multiple factors. Existing practice of drinking water vaccine delivery should also be revised to better the outcome of this vaccine administration method.